Gender Representation in the Novel Tarian Bumi: A Study of Feminism and Masculinity - Weldima Yudit Tiwery; Muta'alim; Muhammad Yunus; Jamson Siallagan; Muhalli (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2024)
While previous studies on Indonesian literature have explored gender themes, limited attention has been given to how Balinese cultural constructs influence gender representation in novels. This study examines Oka Rusmini's novel Tarian Bumi through feminist and masculinity perspectives to address this gap. The data in this study consists of sentences, characters, symbols, gender roles, and cultural aspects, which are taken from the novel Tarian Bumi. The method used is the free listening method with conversational involvement, where the researcher listens to sentences that contain elements of character, symbol, gender roles, and cultural aspects that influence gender construction in Balinese society through listening and note-taking techniques. The researcher also collects supporting data through related literature studies. Once the data is collected, the analysis process is carried out through data reduction, classification, verification, tabulation, and interpretation, and ultimately produces conclusions. The findings indicate that Tarian Bumi presents a diverse and complex representation of gender, where gender roles are not always confined to the stereotypical roles commonly found in Balinese society. The novel critiques the patriarchal gender constructs within Balinese culture and provides space for women to express their desires and ambitions, which sometimes conflict with existing social expectations. Furthermore, it depicts contradictory forms of masculinity, where male characters do not always meet the expected standards of masculinity in Balinese society. In conclusion, Tarian Bumi offers a complex gender representation and provides a broader understanding of gender dynamics within Balinese society. This study contributes to the discourse on gender construction in Indonesian literature and encourages the further development of gender studies in the field of literature.